Cost-utility analysis of mogamulizumab in advanced mycosis fungoides and Sezary syndrome cutaneous T-cell lymphoma - Noemi Muszbek; Edit Remak; Qian Xin; Linda McNamara; Trefor Jones (Becaris Publishing Limited, 2023)
Aim: This study assessed the cost-utility of mogamulizumab, a novel monoclonal antibody, versus established clinical management (ECM) in UK patients in previously treated advanced mycosis fungoides (MF)/S ´ ezary syndrome (SS). Materials & methods: Lifetime partitioned survival model based on overall survival, next treatment-free survival and the use of allogeneic stem cell transplant was developed. Inputs were from the pivotal MAVORIC trial, real-world evidence and published literature. Extensive sensitivity analyses were conducted. Results: Discounted incremental quality-adjusted life years (QALYs), costs and incremental cost-effectiveness ratio were 3.08, £86,998 and £28,233. Results were most sensitive to the survival extrapolations, utilities and costs after loss of disease control. Conclusion: Mogamulizumab is a cost-effective alternative to ECM in UK patients with previously treated advanced MF/SS.